Res Non Verba: Economic Reform S Evaluation in Authoritarian Regimes in South Korea and Chile, 1961-1989 - Ross-Orellana, C (UNIV SANTIAGO CHILE, INST ESTUDIOS AVANZADOS, 2022)
In last decades, neoliberal models of South Korea and Chile have been celebrated as exemplifier models of economic success. Nonetheless, both countries were criticized due the existence of military governments before their economic growth. We argue as hypothesis the reforms and design of new economic benchmarking process in both regimes explains the observed economic success. Concretely, both reforms follow their respectively Path Dependence: meanwhile Park implements an Export Oriented Industrialization (EOI) using Five Years Plans as a base, Pinochet returns to a Primary Exports Model (PEM) combining a closed economy monetarism (1973-1981) to pass just after to an open economy deindustrialization (1982-1989). Due both strategies and path dependencies are different, results will differ concerning WHEN economic growth occurs: with Park, will occur during his government; in the case of Pinochet, after his scavenging.